Determination of Teaching Experience, Competence, and Work Environment on the Performance of Teachers of SMP Negeri 1 Peureulak, East Aceh Regency - Sumedi, Rahmad; Firmansyah, Firmansyah; Maulina, Nur Afni; Liswandar, Alfian; Panjaitan, Robinhood Setiawan; Lubis, Hasrita (Mahesa Research Center, 2025)
This study aims to analyze the influence of teaching experience, competence, and work environment on teacher performance at SMP Negeri 1 Peureulak, East Aceh. The research sample consisted of 47 teachers, who were selected through a total sampling technique. The method used is multiple linear regression, with validity, reliability, and classical assumption tests to ensure the accuracy of the results. The results of the study show that these three variables have a significant effect on teacher performance, both partially and simultaneously. Teacher competence has the most dominant influence, followed by the work environment and teaching experience. Teaching experience contributes to shaping teachers' expertise and confidence in managing the classroom. Teacher competence, especially in pedagogic and professional aspects, has proven to be very decisive in learning effectiveness. A supportive work environment, including relationships with colleagues and school facilities, also plays an important role in improving teacher performance. Simultaneously, these three variables explain 64.8% of the variation in teacher performance. The implications of this study emphasize the importance of developing teacher competencies through continuous training and improving the work environment to support the improvement of teacher performance.